2005
DOI: 10.1530/eje.1.01840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin and ethinyl estradiol–cyproterone acetate on lipid levels in obese and non-obese women with polycystic ovary syndrome

Abstract: Objective: Women with polycystic ovary syndrome (PCOS) exhibit risk factors for cardiovascular diseases such as abdominal obesity, insulin resistance and dyslipidemia. Insulin sensitizers, especially metformin, have been shown to improve these metabolic disturbances, but there are only a few studies on their effects on serum lipids in polycystic ovary syndrome. Methods: Thirty-five women with PCOS (18 obese and 17 non-obese) were randomized to 6-month treatments with metformin or ethinyl estradiol -cyproterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 49 publications
5
30
0
1
Order By: Relevance
“…Thus, here we demonstrate for the first time a positive effect of metformin on the low-grade chronic inflammation, both leukocyte counts and CRP in PCOS women. The decrease in serum CRP levels during metformin therapy is in accordance with the known beneficial metabolic effects of this drug and suggests that CRP or other inflammatory parameters could be used as markers for the efficiency of therapy in PCOS (37). However, our group recently demonstrated that CRP levels also improved after a 3-month well-structured exercise training program in PCOS patients, showing the beneficial effects of a nonpharmacological therapeutic strategy (18).…”
Section: Discussionsupporting
confidence: 53%
“…Thus, here we demonstrate for the first time a positive effect of metformin on the low-grade chronic inflammation, both leukocyte counts and CRP in PCOS women. The decrease in serum CRP levels during metformin therapy is in accordance with the known beneficial metabolic effects of this drug and suggests that CRP or other inflammatory parameters could be used as markers for the efficiency of therapy in PCOS (37). However, our group recently demonstrated that CRP levels also improved after a 3-month well-structured exercise training program in PCOS patients, showing the beneficial effects of a nonpharmacological therapeutic strategy (18).…”
Section: Discussionsupporting
confidence: 53%
“…Although the action of this biguanide on improving lipid metabolism has been widely reported (Caballero 2004, Dominguez & Sowers 2005, Rautio et al 2005, our data represent the first evidence that metformin modulates the production of ovarian prostaglandins.…”
Section: Discussionmentioning
confidence: 56%
“…Study results regarding the effects of metformin on primary prevention of CVD are not coherent (Moghetti, Castello et al 2000;Diamanti-Kandarakis, Alexandraki et al 2005;Rautio, Tapanainen et al 2005). Metformin has a little influence on body weight (less than 2-3% of BMI) (Moghetti, Castello et al 2000;Rautio, Tapanainen et al 2005;Nieuwenhuis-Ruifrok, Kuchenbecker et al 2009) and may ameliorate atherogenic dyslipidemia, raising HDL-C and lowering triglycerides (Rautio, Tapanainen et al 2005;Trolle, Flyvbjerg et al 2007).…”
Section: Metforminmentioning
confidence: 99%
“…Metformin has a little influence on body weight (less than 2-3% of BMI) (Moghetti, Castello et al 2000;Rautio, Tapanainen et al 2005;Nieuwenhuis-Ruifrok, Kuchenbecker et al 2009) and may ameliorate atherogenic dyslipidemia, raising HDL-C and lowering triglycerides (Rautio, Tapanainen et al 2005;Trolle, Flyvbjerg et al 2007). Nevertheless, no alterations in HDL-C or triglycerides were seen in some studies (Banaszewska, Pawelczyk et al 2009).…”
Section: Metforminmentioning
confidence: 99%
See 1 more Smart Citation